Government Budget, and Health Insurance for Public Health in East Java Province - Sony Kristiyanto (MediaTrend, 2021)
One of the conditions needed for development to be carried out properly is the condition of a healthy community. Without a healthy community, development in one area cannot be done well. Health itself is more a public good than a private good, so in this case government intervention is absolutely necessary. This research tries to look at several factors which are predicted to be able to influence the condition of public health. Some of these factors are the availability of infrastructure in the health sector, the government budget and public participation in health insurance issued by the government. Using data between 2017 and 2019 in 38 districts in East Java Province, it was found that only the public participation variable in health insurance issued by the government had a positive and significant impact, while the other variables did not affect the health condition of the community. The behavior of people in Indonesia who tend to register for health insurance if they have experienced health problems is one indication of a positive relationship between public health conditions and the number of participants in government health insurance.